2006
DOI: 10.1523/jneurosci.0526-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Directly Inhibits Primitive Neural Stem Cell Survival But Promotes Definitive Neural Stem Cell Survival

Abstract: There are two types of neural stem cells (NSCs). Primitive NSCs [leukemia inhibitory factor (LIF) dependent but exogenous fibroblast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 43 publications
8
71
0
Order By: Relevance
“…Few NSCs were growing in the vehicle conditions, whereas NSCs were more abundant after ALA treatment (Figure 2b). This observation was confirmed by immunohistochemistry using Ki-67 nuclear protein staining, the expression of which is strictly associated with cell proliferation and is routinely used as a proliferation marker (Wada et al, 2006;Maysami et al, 2008). Indeed, after 3 days of ALA treatment, a nearly 1.6-fold increase in the percentage of Ki-67-positive NSCs was seen (36.5 ± 2.9% of Ki-67-positve NSCs reached 58.1±3.3% in presence of 100 mM ALA, po0.001), clearly indicating an increase in cell division and marked NSC proliferation (Figure 3c, right panel).…”
Section: Ala Treatment Triggers In Vitro Bdnf Expression and Promotesmentioning
confidence: 73%
“…Few NSCs were growing in the vehicle conditions, whereas NSCs were more abundant after ALA treatment (Figure 2b). This observation was confirmed by immunohistochemistry using Ki-67 nuclear protein staining, the expression of which is strictly associated with cell proliferation and is routinely used as a proliferation marker (Wada et al, 2006;Maysami et al, 2008). Indeed, after 3 days of ALA treatment, a nearly 1.6-fold increase in the percentage of Ki-67-positive NSCs was seen (36.5 ± 2.9% of Ki-67-positve NSCs reached 58.1±3.3% in presence of 100 mM ALA, po0.001), clearly indicating an increase in cell division and marked NSC proliferation (Figure 3c, right panel).…”
Section: Ala Treatment Triggers In Vitro Bdnf Expression and Promotesmentioning
confidence: 73%
“…VEGF is reported to stimulate adult neurogenesis in vivo (20,21) and proliferation of brain-derived neural stem/progenitor cells in vitro (22,23). We have reported that VEGF-Flk-1 signaling underlies ECS induction of hippocampal cell proliferation (17) and importantly, rescues hippocampal cell proliferation after irradiation exposure (24).…”
Section: Discussionmentioning
confidence: 97%
“…An increasing number of reports suggest that VEGFA has direct effects on nonvascular cells including neuronal cells (Marti & Risau 1998, Wada et al 2006, Nishijima et al 2007), muscle cells (Germani et al 2003, Bryan et al 2008, and granulosa cells (Greenaway et al 2004). Data also suggest potential functional roles for VEGFA in the postnatal testis, as KDR and FLT1 are expressed in testicular germ cells in humans (Ergun et al 1997), rats (Rudolfsson et al 2004), and mice (Nalbandian et al 2003), while somatic Sertoli and Leydig cells produce VEGFA (Liu & Yang 2004).…”
Section: Introductionmentioning
confidence: 99%